The Limits of Deadly Force in Indonesian Self-Defense Law from a Human Rights Perspective - Irfan Nurhakim (Penerbit Goodwood, 2026)
Purpose: This study examines the limits of deadly force in self-defense under Indonesian criminal law from a human rights perspective, focusing on whether the principles of necessity and proportionality adequately protect the right to life while ensuring legal certainty. Research Methodology: This study employs a normative juridical method combined with qualitative case analysis. It reviews Article 49 of the former Criminal Code and Articles 34 and 35 of the 2023 Criminal Code, as well as selected judicial decisions, including Supreme Court Decision No.566 K/Pid/2025. The analysis is framed by Article 6 of the ICCPR and General Comment No. 36. This study is doctrinal and review-based, utilizing systematic statutory interpretation and case analysis. Results: The findings show that the Indonesian self-defense law is normatively restrictive and aligned with the protection of the right to life. The cumulative requirements of unlawful attack, immediacy, necessity, and proportionality reflect a life-protective orientation. However, judicial reasoning often lacks a structured proportionality analysis and consistent articulation of necessity, particularly regarding retreat opportunities and psychological disturbance, resulting in operational inconsistency. Conclusions: Indonesian law adequately limits deadly force in principle but requires clearer methodological articulation in judicial practice to enhance legal certainty and coherence with the human rights standards. Limitations: This study relies on qualitative doctrinal analysis of selected cases without quantitative data, which may limit the generalizability of its findings. Contributions: This study contributes to criminal law and human rights scholarship by clarifying the doctrinal limits of self-defense in Indonesia.